Transcatheter closure of large postinfarct ventricular septal defect: Initial results of prototype Occlutech® device including the first‐in‐human. Issue 3 (25th February 2023) - Lee, Kuo Ting; Taliotis, Demetris; Hamilton, Mark; Manghat, Nathan; Bedair, Radwa; Turner, Mark
Abstract: Background: Postinfarct ventricular septal rupture is a serious complication in delayed or failed reperfusion with a grim prognosis. The optimal timing and treatment option remain debatable in the absence of randomized controlled trials. Percutaneous device closure is a well‐reported and less invasive treatment option but recent imaging studies indicate that majority of defects are too large to be adequately covered by the currently Conformite Europeenne and Food and Drug Administration approved occluder devices. Methods: Six patients presented with large and complex postinfarct ventricular septal ruptures, considered unsuitable for the Amplatzer post‐infarct ventricular septal defect Occluder, so were treated using the prototype Occlutech® 36 mm PI‐VSD occluder, including the first‐in‐human use. Results: The prototype device was successfully deployed in all patients with satisfactory immediate results and shunt reduction. Three patients (50%) in cardiogenic shock did not survive beyond discharge, of which two were complicated by device dislodgement or embolization. Conclusions: Percutaneous closure of large postinfarct ventricular septal ruptures is possible using newer device with a wider coverage. Further device refinement is necessary to improve treatment outcomes.